PS-C17-8: PREVALENCE OF PREDIABETES IN PATIENTS WITH ACUTE CORONARY SYNDROME. (January 2023) - Pandey, Naveen Kumar; Karki, Biplave; Karki, Prahlad
Abstract : Objective: Prediabetes is defined as an intermediate metabolic state between normoglycaemia and diabetes and includes those with impaired glucose tolerance and impaired fasting glucose. Diabetes mellitus is a well recognised risk factor for cardiovascular disease and acute coronary syndrome. However, evidence is limited regarding the prognostic value of 'prediabetes' on the clinical outcome of ACS. The objective of this study was to know the prevalence of prediabetes in ACS. Design and methods: This was a single center descriptive cross-sectional study to know the prevalence of prediabetes in 115 patients consisting of 71 males and 44 females, admitted with ACS in the Department of Cardiology between August 2020 to July 2021 Results: Based on the definition of the American Diabetes Association, 35 (30.4%) patients were newly diagnosed diabetic, 46 (40%) patients were prediabetic and 34(29.6%) were non-diabetic. Based on HbA1c alone, 26.1% patients were classified as newly diagnosed diabetic patients, 38.3% patients were classified as prediabetic and 35.7% as non-diabetic. Compared with patients without diabetes, patients with prediabetes tended to have a longer hospital stay (p = 0.04), higher creatinine level (p = 0.01) and higher incidence of heart failure (p = 0.046). Conclusion: Prediabetes is common in patients presenting with ACS who are not previously known to have diabetes. Further multi-center studies with long term clinical follow-up are needed to draw a firm conclusion regarding the impact of prediabetes on clinical outcome.